Analysis of Robert K. Merton's Adaptation Typology in the Implementation of Social Reintegration Program of Correctional Client, Case Study: Sintang Correctional Center, Indonesia - Fajar, Udik; Murakami, Tadashi (Restorative : Journal of Indonesian Probation and Parole System, 2024)
Abstract. This study investigates the social reintegration programs for correctional clients at Sintang Correctional Center in Indonesia, utilizing Robert K. Merton's adaptation typology to analyze the pathways of ex-prisoners during their reintegration process. Emphasizing the rights of prisoners as outlined in Indonesian law, the research highlights the significance of effective community guidance in mitigating recidivism and facilitating successful adaptation. Using a qualitative approach including phenomenological method and in-depth interview on 20 correctional clients, the study identifies the challenges faced by ex-prisoners, including economic hardship and societal stigma, which impede their reintegration efforts. The educational backgrounds of participants reveal a concerning lack of higher education, further limiting employment opportunities. The community guidance program is structured in three stages, namely early, advance, and final stage, which aims to enhance the quality of life for these individuals. However, findings indicate that a majority of such programs remain engaged in case work rather than group activities, suggesting areas for program improvement. By applying Merton's typology, the study categorizes clients' adaptation experiences into Conformity, Retreatism, and Innovation, illustrating the diverse strategies employed by ex-prisoners in navigating their reintegration. The findings underscore the necessity for comprehensive community support systems that address the multifaceted challenges faced by correctional clients, ultimately aiming to reduce recidivism and promote successful societal reintegration. Future recommendations include enhancing educational and vocational training opportunities and fostering community acceptance to improve reintegration outcomes.